Mean Platelet Volume Is Related to Cumulative Disease Damage in Patients with Systemic Lupus Erythematosus - Yolanda Fernández-Cladera; Marta Hernández-Díaz; María García-González; Juan C. Quevedo-Abeledo; Adrián Quevedo-Rodríguez; Fuensanta Gómez-Bernal; Cristina Gómez-Moreno; Candelaria Martín-González; Miguel Á. González-Gay; Iván Ferraz-Amaro (Life, 2024)
Mean platelet volume (MPV), which represents the average platelet size in femtoliters, has emerged as a reliable biomarker in several systemic and chronic disorders. However, its relationship with disease characteristics in large series of patients with systemic lupus erythematosus (SLE) has not been exhaustively studied to date. In the present work, we aimed to analyze how disease characteristics, including disease activity and cumulative damage, relate to MPV in a well-characterized series of SLE patients. In total, 179 patients with SLE and 181 age- and sex-matched healthy controls were recruited. Complete blood counts including MPV were assessed. Linear multivariable analysis was performed to evaluate the relationship between MPV and SLE disease characteristics, including composite scores of disease activity and damage. MPV was significantly lower in patients with SLE compared to controls after multivariable analysis (beta coefficient, −0.7 [95% confidence interval, −1.1 to −0.3)] fL, p < 0.001). Although the SLEDAI disease activity index was not related to MPV, the SLICC score measuring cumulative disease damage was significantly associated with lower MPV values after adjustment for covariates. Elements of the SLICC score that were associated with lower MPV levels were those pertaining to the kidney, peripheral vascular, and musculoskeletal manifestations of the disease. In conclusion, MPV is lower in patients with SLE compared to matched controls. This MPV downregulation is primarily due to the renal, peripheral vascular and musculoskeletal manifestations of the disease. MPV may represent a biomarker of accrual disease damage in SLE.